1979
DOI: 10.1071/ea9790716
|View full text |Cite
|
Sign up to set email alerts
|

Populations of honeybees pollinating sunflower crops on the central Darling Downs, Queensland

Abstract: Populations of honeybees pollinating flowering sunflower heads in 42 fields on the central Darling Downs were recorded. Mean populations ranged from 21.9 to 171.2 bees per 100 flowering heads. A calculated maximum requirement for the region during fine weather amounted to 24 bees per 100 flowering heads. Populations were positively correlated with number of hives within 3 km of fields. In 18 fields with no hives within 3 km, mean populations (apparently from feral colonies) ranged from 21.9 to 130.9 bees per 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The conventional strip count method was followed, as described by Free (1964); Benedek et al (1972); Langridge & Goodman (1974); Radford et al (1979) and Parker (1981). Species diversity and abundance were determined for randomly-selected plant rows.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional strip count method was followed, as described by Free (1964); Benedek et al (1972); Langridge & Goodman (1974); Radford et al (1979) and Parker (1981). Species diversity and abundance were determined for randomly-selected plant rows.…”
Section: Methodsmentioning
confidence: 99%
“…Although modem hybrid sunflower cultivars are bred to have a self-pollination efficiency of up to 50%, insects are internationally reported to be the primary cross-pollinators of sunflower: in the United States (McGregor, 1976;Hurd et al, 1980), eastern Europe (Benedek, Manninger & Nagy, 1972), India (Goyal & Atwal, 1973), Argentina (De Diez, 1979) and Australia (Langridge & Goodman, 1974;Radford, Rhodes & Nielsen, 1979). Pollinators listed by .these authors included not only beneficial insects such as honeybees and solitary bees, but also agricultural pests such as American bollworm (larvae and moths) and spotted maize beetles.…”
Section: Introductionmentioning
confidence: 99%
“…Several accounts of honeybee activity in sunflower fields exist (Free, 1964;Langridge & Goodman, 1974;Radford, Rhodes & Nielson, 1979;Krause & Wilson, 1981;Parker, 1981). these authors found that honeybee activity revealed a pattern on a daily basis and with the ageing of the sunflower field.…”
Section: Introductionmentioning
confidence: 96%